Utility of P63 in Differentiating Giant Cell Tumor from Other Giant Cell-Containing Lesions - Monalisa HUI; Shantveer G UPPIN; K Karun KUMAR; S RADHIKA; P CHANDRASEKHAR; K Nageshwara RAO (Federation of Turkish Pathology Societies, 2022)
Objective: To assess P63 expression in giant cell-containing lesions of the bone (GCLB) and to determine its utility in differentiating giant cell tumor of the bone (GCTB) from other GCLBs. Material and Method: Cases diagnosed as GCLB on histopathology were included in the study. P63 immunohistochemistry was performed in all the cases. The percentage of cells showing nuclear positivity was assessed in the non-giant cell component. Statistical analysis was performed using the Mann-Whitney U test. Results: Of the total 53 cases studied, the majority were GCTBs (23), followed by 12 cases of chondroblastomas (CBL) and 18 other giant cell lesions (GCLs). All giant cell-containing lesions except one case of CBL and brown tumor of hyperparathyroidism (BTH) showed P63 staining in the non-giant cell component. However, the mean P63 labeling of GCT (52.6%) was higher compared to CBL (28.3%), aneurysmal bone cyst (ABC) (15.2%), non-ossifying fibroma (NOF) (24.5%), giant cell lesion of small bones (GCLSB) (11%), BTH (6.8%) and chondromyxoid fibroma (CMF) (12.3%), with a p-value of <0.001. Conclusion: Although p63 was present in majority of the GCLBs, its percentage positivity was significantly higher in GCTB compared to the other GCLBs. The diagnosis of GCTB is likely if cut-off value of >50% is applied.